2014
DOI: 10.15288/jsads.2014.s17.98
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Alcohol and Other Drug Control Policy Research

Abstract: ABSTRACT. Objective:This article provides a historical review of alcohol and other drug policy research and its impact on public health over the past 75 years. We begin our summary with the state of the fi eld circa 1940 and trace the development across the subsequent decades. We summarize current thinking and suggest possible future directions the fi eld of alcohol and other drug policy may take. Specifi c topics discussed include the minimum legal drinking age, pricing and taxation, hours and days of sale, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 88 publications
2
21
0
1
Order By: Relevance
“…In contrast, Anderson, Chisholm, and Fuhr's (2009) review revealed little evidence that workplace alcohol policies result in changes to drinking norms or reduce harmful drinking behaviour. Another problem is that policy evaluations have traditionally focused on the establishment of policies and not the outcomes or knowledge of why and how they work (Treno, Marzell, Gruenewald, & Holder, 2014).…”
Section: Previous Research and Theoretical Frameworkmentioning
confidence: 99%
“…In contrast, Anderson, Chisholm, and Fuhr's (2009) review revealed little evidence that workplace alcohol policies result in changes to drinking norms or reduce harmful drinking behaviour. Another problem is that policy evaluations have traditionally focused on the establishment of policies and not the outcomes or knowledge of why and how they work (Treno, Marzell, Gruenewald, & Holder, 2014).…”
Section: Previous Research and Theoretical Frameworkmentioning
confidence: 99%
“…For many years the alcoholic beverage control policies that aim to control and reduce the consumption of alcoholic beverages and drinking-related harms have been applied and evaluated (Babor et al, 2003(Babor et al, , 2010Anderson, 2009;Rabinovich et al, 2009;Patra, Giesbrecht, Rehm, Bekmuradov, & Popova, 2012;Anderson & Møller, 2012;Treno, Marzell, Gruenenwald, & Holder, 2014). However, although they are often shown to be effective in well-defined experimental contexts of observation, needed generalizable evidence is frequently missing at the macro country level.…”
Section: Prevention: Alcoholic Beverage Control Policiesmentioning
confidence: 99%
“…Alcohol policy-making at the local level is of increasing importance (Giesbrecht, 2007;Holmila & Warpenius, 2007) and several effective policy measures are decided on and enforced at the local level (Treno, Marzell, Gruenewald, & Holder, 2014). The efficacy and effectiveness of alcohol policies at the local level have been assessed in many studies (Babor et al, 2010;Treno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy and effectiveness of alcohol policies at the local level have been assessed in many studies (Babor et al, 2010;Treno et al, 2014). In particular, policies that regulate the availability of alcohol in terms of outlet density and trading hours have been shown to be effective in reducing drinking and related harm (Babor et al, 2010; Campbell et al, 2009; Hahn et al, 2010;Popova, Giesbrecht, Bekmuradov, & Patra, 2009).…”
Section: Introductionmentioning
confidence: 99%